A New Generation of Furanic Copolyesters with Enhanced Degradability: Poly(ethylene 2,5-furandicarboxylate)-co-poly(lactic acid) Copolyesters - Matos, Marina
2,5-Furandicarboxylic acid is a promising renewable-based monomer essentially used in polymer synthesis to prepare renewable-based counterparts to petrochemical polyesters. In general, they are entirely based on renewable resources and have a myriad of very interesting thermal and mechanical properties; however, this study is the first to tackle their (bio) degradability, a worldwide-demanded property. To address this demand, an entirely new generation of furandicarboxylate-derived copolyesters, based on both poly(ethylene 2,5-furandicarboxylate) (PEF) and poly(lactic acid) (PLA), is developed for the first time. These copolyesters are characterized by several techniques, including attenuated total reflectance-Fourier transform IR (ATR-FTIR), H-1, and C-13 NMR spectroscopy, thermogravimetric analysis (TGA), DSC, and X-ray diffraction (XRD), and their degradability behavior is evaluated by water-absorption studies and hydrolytic degradation. They are essentially stiff amorphous polymers possessing high T(g)s, e.g., ca. 69 degrees C for 29% of lactyl units. Importantly, the data show also that they have improved degradability when compared with the PEF homopolyester counterpart.